2016
DOI: 10.3389/fpls.2016.01114
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Oscillation of the Lettuce Transcriptome under Constant Light and Light–Dark Conditions

Abstract: Although, the circadian clock is a universal biological system in plants and it orchestrates important role of plant production such as photosynthesis, floral induction and growth, there are few such studies on cultivated species. Lettuce is one major cultivated species for both open culture and plant factories and there is little information concerning its circadian clock system. In addition, most of the relevant genes have not been identified. In this study, we detected circadian oscillation in the lettuce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
4
23
0
Order By: Relevance
“…So, our results suggest that there are two subgroups of circadian genes: one group with oscillation behavior both at light-dark condition and continuous light are only regulated by core clock mechanism, while the other group with continuous light-specific oscillation are regulated by core clock mechanism and also by another pathway that is effective at light-dark condition. Our result is consistent with the conclusion of a previous study in which they adopted a different approach for rhythmicity analysis (35) and also with the finding of a recent study showing continuous-dark specific oscillation in the liver of mice (44) We also observed the same phenomenon with the oscillating AS and APA events: some events became rhythmic only under constant light, and the oscillation profiles of AS and APA events dramatically altered with the change of light regimen. All these suggest that plants organize genome-wide transcriptional and posttranscriptional oscillation according to the timing and duration of light and dark periods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…So, our results suggest that there are two subgroups of circadian genes: one group with oscillation behavior both at light-dark condition and continuous light are only regulated by core clock mechanism, while the other group with continuous light-specific oscillation are regulated by core clock mechanism and also by another pathway that is effective at light-dark condition. Our result is consistent with the conclusion of a previous study in which they adopted a different approach for rhythmicity analysis (35) and also with the finding of a recent study showing continuous-dark specific oscillation in the liver of mice (44) We also observed the same phenomenon with the oscillating AS and APA events: some events became rhythmic only under constant light, and the oscillation profiles of AS and APA events dramatically altered with the change of light regimen. All these suggest that plants organize genome-wide transcriptional and posttranscriptional oscillation according to the timing and duration of light and dark periods.…”
Section: Discussionsupporting
confidence: 93%
“…1A, Supplemental Fig. S1A), similar to the observation in lettuce (35). Our RT-qPCR analyses of LHCA6 and RBCS2B genes verified that these genes oscillate under continuous light, but not at light-dark condition.…”
Section: Non-homogeneous Circadian and Diurnal Oscillation Patterns Asupporting
confidence: 83%
“…Most estimates of daily gene expression patterns have been determined for protein-coding genes using gene or genome tiling microarrays (Edwards et al, 2006;Covington et al, 2008;Michael et al, 2008b;Hazen et al, 2009;Khan et al, 2010;Filichkin et al, 2011). More recently, RNAseq was applied to measure diurnal or circadian-associated transcript expression in sugarcane (Saccharum officinarum), S. viridis, Sedum album, lettuce, Douglas fir, Physcomitrella patens, and several algal species (Hotta et al, 2013;Zones et al, 2015;Higashi et al, 2016;Cronn et al, 2017;Huang et al, 2017;Ferrari et al, 2019;Wai et al, 2019). Estimates for the proportion of protein-coding genes that are controlled by the circadian clock generally range between 6% and 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Given the nature of circadian rhythm, time-series experiments coupled with transcriptome studies represent key steps towards understanding the complex sensing and signalling process of photoperiod changes (Doherty & Kay, 2010). Although many RNA-seq studies have provided a global perspective that describes the contribution of circadian rhythmic to gene regulation networks in plants (Higashi, Aoki, Nagano, Honjo, & Fukuda, 2016;Khan, Rowe, & Harmon, 2010;Michael et al, 2008;Xu et al, 2011), most studies focus on day-night cycles under certain day-length conditions or circadian rhythms under constant light conditions. Few studies to date have globally examined the impact of day length on the diurnal rhythmic patterns of the transcriptome (but see Dalchau et al, 2010;Michael et al, 2008).…”
mentioning
confidence: 99%